(untitled) (Medico Legal Update, 2020)
Background/Objectives: The goal of this study was to survey the influence on intervention of task-based upper limb training on activities of daily living and upper limb function in chronic stroke patients. Method/Statistical Analysis: 32 patients were randomly divided to into two groups. For the affected upper limb, the experimental group (N=16) applied the task-based training program (TBTP) and the control group (N=16) performed the non-task-based training (NTBT). Both groups executed 5 times per week, 30 minutes per session for 4 weeks. The paired t-test was used to compare before and after intervention results of each group. The independent t-test was used to compare changes in results between the groups. Findings: In the TBTP group, the pre-intervention of Fugl-Meyer assessment (FMA) is 46.75 ± 3.75 and the post-intervention score is 50.88±4.92. In the NTBT group, the FMA had a pre-intervention score of 47.44±4.44 and a post-intervention score of 49.13±5.14. Both groups showed statistically significant differences before and after intervention (p<0.01). In the TBTP group, the pre-intervention score of Korean versions of modified Barthel Index (K-MBI) was 73.31 ± 6.91 and the post-intervention was 79.00±6.96 (p<0.01) after intervention. The K-MBI score of the NTBT group in before intervention was 78.63±6.32, after intervention 73.81±6.01. Both groups showed significant differences before and after intervention (p>0.05). In all assessments, no differences were observed between groups before and after intervention. Improvements/Applications: This study did not show that TBTP is more effective than NTBT in improving the daily activities and upper limb function of stroke patients.